2019
DOI: 10.3329/bjms.v18i4.42915
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomes of Cancerous and Normal cells in Response to Low-energy/low-dose Medical Diagnostic X-rays

Abstract: Background: Low-energy/low-dose ionizing radiation is increasingly being used in medical diagnosis, yet the effects of low-energy/low-dose medical diagnostic X-rays on biological systems remains a mystery. Thus, the aim of this present study is to determine the characteristics of lysosomes of cancerous and normal cells in response to low-energy/low-dose medical diagnostic X-rays. Methods and materials: Three cell lines composed of peripheral blood mononuclear cells (PBMCs), adriamycin-sensitive erythrole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Whereas, Tungjai used PBMC as a normal cell model to determine intracellular organelles characteristic such as lysosomes in response to low-dose medical diagnostic X-rays 24 . Although PBMC has been widely used as a diagnostic tool, it is predicted that these cells may provide additional benefits to cure diseases, especially in tissue engineering therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, Tungjai used PBMC as a normal cell model to determine intracellular organelles characteristic such as lysosomes in response to low-dose medical diagnostic X-rays 24 . Although PBMC has been widely used as a diagnostic tool, it is predicted that these cells may provide additional benefits to cure diseases, especially in tissue engineering therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our in vitro data using these three biological endpoints suggests that the medical diagnostic low-dose X-rays do not induce any detrimental effects on human PBMCs.This is consistent with our previous studies that showed no changes the mitochondrial membrane potential, number of apoptotic cells, or cell cycle in lymphocytes exposed to radiation at 0.03, 0.05, or 0.1 mGy of (70 kV) medical diagnostic X-rays when compared to the corresponding nonirradiated cells at all collecting timepoints 31 . However, lowdose medical diagnostic X-rays might affect to the function of lysosome of cancer cells 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Lysosomal function was studied by altering the accumulation of acridine orange (AO) in lysosomes. The staining method was modified from a previously published work 33,34 . Briefly, 10 6 cells were suspended in 2 mL PBS buffer, pH 7.25 at 37°C in the presence of 1µM AO for 5 minutes in the dark.…”
Section: Lysosomementioning
confidence: 99%